The Influence of The Interaction Between Simvastatin and Grapefruit Juice (Citrus Maxima Merr.) on The Anticholesterol Effects of Male Mice - Humaidah, Daffa; Widodo, Gunawan Pamudji; Widyasti, Jena Hayu (Jurnal Farmasi & Sains Indonesia, 2022)
Consumption of drugs together with herbal medicine at the same time can affect its efficacy. Cholesterol can be treated with simvastatin and herbal medicine such as grapefruit (Citrus maxima Merr.) which contains phenols and flavonoids as anticholesterol and furanocoumarins. This study aims to determine whether the consumption of simvastatin and grapefruit together will affect the anticholesterol effect. Male mice of 35 Swiss strains were divided into 7 groups, each consisting of 5 mice. Without treatment, negative control Na-CMC 0.5%, positive control I simvastatin 5.2 mg/kgBW mice, positive control II grapefruit juice 26 mL/kgBW mice, interaction I, II and III simvastatin 5.2 mg/ kgBW of mice and grapefruit juice were 13 mL/kgBW, 19.5 mL/kgBW, and 26 mL/kgBW of mice, respectively. All groups except without treatment were given a high-fat diet consisting of lard, duck egg yolk, and chicken liver and were induced with 0.1% propylthiouracil solution for 28 days before treatment. Total cholesterol levels were measured after 28 days of induction and 35 and 42 days after treatment. The interaction of simvastatin and grapefruit juice can affect the anticholesterol effect in the form of increasing the effect of reducing total cholesterol levels in the blood of mice. The effective interaction dose was the interaction dose I (simvastatin 5.2 mg/kg BW of mice and grapefruit juice 13 mL/kg BW of mice) which had an anticholesterol effect compared to the single dose group of simvastatin and grapefruit juice.